Analysis of failure frequency and failure rate of RF/ antenna subsystems for an earth station system - Abdul Rahim, Nadirah; Abdul Rahman, Nur Shazana; Abdoli, Shiva; Jeevan Rao, Subramaniam; Mohamad Mokhtar, Mohammed Imtiaz (Anka Publishers, 2022)
During the system design process, telecommunications engineers usually identify failure rate and failure in time (FIT) values when stipulating subsystems or components in an earth station system. Failure rates are hardly revealed by vendors as time-dependent values. Therefore, they must be cautiously assessed when used in reliability analysis. Most vendors share this information as Mean Time Before Failure (MTBF) which is a general figure for equipment to indicate a failure. In this paper, the external factors, such as power supply issues, lightning strike and human error were not considered. The failure frequency and failure rate are crucial for engineers to identify which subsystem always fails and which is not. In this paper, the analysis of failure rate and failure frequency were simulated based on the data provided by MEASAT for the RF/Antenna subsystems of an earth station system. Then, from this analysis, the engineers can design a back-up plan to make sure that the transmission is not disrupted. The parallel configuration was also adopted in this research consisting of 2-parallel, 3-parallel, and 4-parallel configurations. From this analysis, it can be concluded that the 2-parallel configuration yields the highest total failure frequency with 13 failures at MTBF of 10th year. In turn, the HPA subsystem was identified to have the highest number of failures as compared to other subsystems in each configuration because it was sensitive to lighting strikes. Furthermore, the total failure rate gradually decreased as the MTBF increased because the number of failure frequency was low at each MTBF for each subsystem in each configuration.